Adaptive change management strategies for aligning organizational teams with volatile digital consumer trends - Skochko, Olga (Актуальні питання економічних наук, 2025)
The relevance of the study is determined by the growing need for innovative management approaches to ensure the effective functioning and development of organizations in an unstable business environment. The purpose of the article is to review the effectiveness of adaptive change management strategies for aligning organizational teams with evolving trends in digital consumption. Methods. To study current developments in the field, an analysis of the scientific literature was conducted, and to present the results, generalization and systematization were employed. Results. Methodological approaches to the analysis of adaptive change management strategies were considered, in particular, the application of systems analysis to study organizational transformations, the use of digital analytics tools to interpret consumer trends, and the assessment of the effectiveness of team interaction in digital work environments. The impact of digital consumer behavior on the transformation of management approaches was analyzed, particularly in light of the growing importance of cross-functional cooperation, rapid decision-making, and data integration into management practices. The paper examines the mechanisms for aligning organizational teams with changing consumer expectations and highlights the role of digital communication platforms, collaboration tools, and real-time data analytics in facilitating coordinated organizational responses to market changes. The paper assesses key factors that influence team effectiveness when implementing adaptive change management strategies, including developing digital competencies in employees, fostering a collaborative culture in the organization, and creating leadership structures that support innovation. Conclusions. Adaptive change management strategies have been shown to significantly enhance organizational teams’ ability to respond to the challenges of the digital economy. Integrating systems-based management, digital consumer analytics, and collaborative team practices can help organizations become more agile, improve coordination among team members, and enable more effective implementation of change initiatives.